Balancing agile combat support manpower to better meet the future security environment - Mills, Patrick, 1975-; Costello, Rachel; Romano, Daniel M.; Ausink, John A.; Drew, John G., 1956- (Research report (Rand Corporation), 2014)
The U.S. Air Force's (USAF's) current approach to sizing and shaping non-maintenance agile combat support (ACS) manpower often results in a discrepancy between the supply of ACS forces and operational demands because much of ACS is sized and shaped to meet the requirements of home-station installation operations, not expeditionary operations. This report proposes a more enterprise-oriented approach to measuring ACS manpower requirements by synthesizing combatant commander operational plans, Defense Planning Scenarios, functional area deployment rules, and subject-matter expert input. Using these new expeditionary metrics to assess the capacity of the current ACS manpower mix to support expeditionary operations, this report finds that there are imbalances among its career fields relative to expeditionary demands. To address these imbalances, it develops and assesses several rebalanced manpower mixes and finds that the USAF can achieve more expeditionary ACS capacity than it currently has by realigning manpower, and it can realize substantial savings by reducing end strength and substituting civilian billets for military billets.